(untitled) (Research, Society and Development, 2020)
This article discusses the importance of existing multilevel libraries in the Federal Network of Vocational and Technological Education aiming at the process of inclusion of users with motor and visual disabilities. The aim of the study is to demonstrate the relevance of this type of library to the teaching-learning process of the entire academic community. To this end, we present a research that envisions the definition of visual and motor disability, highlights the role of laws in the face of guaranteeing the rights of this public and defends access to information as a form of inclusion. As a methodology, qualitative and quantitative research was used. Thus, the instruments were both books, journal articles and laws for qualitative research and a questionnaire for quantitative. It was found that there is an interest of the federal school system in ensuring the rights of students with disabilities and a need for awareness of institutions and society in the process of achieving inclusion in its entirety. In this sense, we can exemplify the Waldyr Diogo de Siqueira Library, as an IFCE Multilevel Library, Fortaleza campus.